“Community hoarding”: a further complication for education research? - Arafeh, Sousan (2025)
Keywords: Computer science; Hoarding (animal behavior); Medicine; dept.edl

Editorial: Educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2019)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Curriculum mapping in higher education: a case study and proposed content scope and sequence mapping tool - Arafeh, Sousan (Journal of Further and Higher Education, 2016)
Best practice in curriculum development and implementation requires that discipline-based standards or requirements embody both curricular and programme scopes and sequences. Ensuring these are present and aligned in course/programme content, activities and assessments to support student success requires formalised and systematised review and development processes. These processes are not always in play in higher education, however. Using a descriptive qualitative case study strategy, this article shares how policy outcomes within intermediate and superintendent certification, sixth-year and Ed.D. doctoral courses and programmes at a state university were reviewed, mapped and assessed using an evidence-based curriculum analysis model and tool that mapped standards and outcomes from course syllabus data. Strengths and weaknesses of this approach are discussed and it is suggested that the field might benefit from a curriculum mapping and analysis method that also considers content coverage. A Course-Level Content Scope and Sequence Mapping Tool, developed to map content scope and sequence alongside standards or outcomes mapping, is presented for consideration and testing. The ability to assess and improve curriculum is only as good as the conceptual frameworks, methods and tools available. This critical case study is one effort to advance the field by drawing attention to the importance of curricular content mapping. The study should be of interest to higher education staff, researchers and accreditors concerned with postsecondary programmes and their curricular scope and sequence coherence, quality and improvement. © 2015 UCU.
Keywords: Curriculum; content; content mapping; curricular content; curricular scope and sequence; curriculum mapping; curriculum mapping tool; dept.edl; educational leadership; higher education; policy; programme coherence

The adaptive challenge of social justice in educational leadership - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Editorial: Further work on educational leadership and social justice - Arafeh, Sousan (Journal of Educational Leadership and Policy Studies, 2020)
Keywords: dept.edl; peer-reviewed; ⛔ No DOI found

Urban tween talk about using mobile phones for learning - Arafeh, Sousan; Kuszpa, M; Weller, M; Mitchell, T (Mobile Learning: Perspectives on Practice and Policy, 2018)
There can be no doubt that mobile technologies are here to stay. Global mobile traffic grew 74 percent in 2015 alone, with 563 million devices and connections added -- most of them tablets and Smartphones. This growth has been 4000-fold in the past 10 years and 400 million-fold in the past 15 years (Cisco, 2016). Mobile technologies permeate the lives of 21st century citizens as mainstays of organizational and institutional day-to-day operations, commerce, and communication and as tools used to support individuals' personal, social, and career responsibilities. In both the corporate and educational worlds, e- and m-learning and marketing with mobile technologies are moving forward at breakneck speed with, in many cases, a blurring of traditional sector boundaries. As neither the technology nor the uses are static, exploring practices and policies that underpin this quickly shifting mobile technology context is crucial for ensuring its intelligent, purposeful, and equitable use. This edited book provides a venue for researchers to share their work on mobile learning with a focus on uses for mobiles in informal settings and PK-20 classrooms, language learning, mobile gaming, leadership and policy issues, and what mobile learning in the future may be. It assists researchers and educators to consider and answer questions such as: What is "mobilelearning" today How can mobiles be used to enable learning How is mobile learning crossing or connecting economic, social, and/or cultural sectors How do specific cultural practices with media influence mobile learning (e.g
Keywords: dept.edl

Educational Leadership: Perspectives on Preparation and Practice - Haynes, Norris M.; Arafeh, Sousan; Magagula, Cynthia McDaniels (University Press of America, ® Inc., 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedagogical and experiential learning models as well as provocative new paradigms of their own to help prepare leaders and reinforce leadership effectiveness.
Keywords: Educational leadership; School management and organization; dept.edl; faculty_collection

Gearing up to GEAR UP: four perspectives on early implementation considerations for GEAR UP - Arafeh, Sousan; Fopiano, Joy; Risisky, Deb; Haynes, Norris M (2012)
Keywords: dept.edl; dept.pch; ⛔ No DOI found

Mobile Learning: Perspectives on Practice and Policy - Herro, Danielle; Arafeh, Sousan; Ling, Richard Seyler; Holden, Chris (Digital media and learning, 2018)
Keywords: Mobile communication systems in education; United States; United States; Internet in education; dept.edl; faculty_collection